(untitled) (Journal of the College of Basic Education, 2022)
The directing in the Iraqi theater began simple and naive, and the representation takes place in it according to general perceptions of events, situations and personalities, and in application of the notes that some authors put on the text. The first pioneers of the Iraqi playwrights, such as Haqi Al-Shibli, Safaa Mustafa, and Jaafar Al-Saadi, did everything from writing or preparing the text, acting it, directing it, and all the details related to the show.